Sensitive allele-specific real-time PCR test for mutations in BRAF codon V600 in skin melanoma - Pisareva, Ekaterina; Gutkina, Nadezhda; Kovalenko, Sergei; Kuehnapfel, Sarah; Hartmann, Arndt; Heinzerling, Lucie; Schneider-Stock, Regine; Lyubchenko, Lyudmila; Shamanin, Vladimir A. (Melanoma Research, 2014)
Mutations at BRAF codon V600 are used as predictive biomarkers for targeted therapy of skin melanoma. Here, a simple sensitive test to detect mutations of BRAF-V600 was developed using real-time PCR with allele-specific primers and TaqMan probes. Two versions of the test using sense and antisense allele-specific primers were designed and evaluated. The test detected 1% mutant allele V600E/K in 10 ng DNA standard made from wild-type human DNA spiked with BRAF-V600E or the V600K plasmid. The test was validated on clinical formalin-fixed paraffin-embedded samples of skin melanoma using pyrosequencing as a reference method. In the clinical samples, we detected the common mutation V600E, as well as the rare mutations V600K, V600E2 (codon GAA), V600E2 K601del, V600D-K601del, and V600R. In comparison with pyrosequencing, both versions of the test had 100% specificity with sensitivities of 97 and 86% for sense and antisense allele-specific primers, respectively. Using the PCR test with sense allele-specific primers, mutations in V600 were found in 33 of 51 Russian patients (64.7%) with cutaneous melanoma. This closed-tube real-time PCR test can be used as a simple and sensitive assay for mutations of BRAF-V600 in cutaneous melanoma.
EVALuna2:6621